Один из ключевых элементов фортификации Калос Лимена (башня № 6) - Кутайсов, В.А. (Археологический альманах, 2012)
Античное городище расположено на межбалочной гряде, между Ак-Мечетским лиманом с юга в устьевой части балок Попова и Кельшейской, и безымянной балкой с севера, в устье которой время от времени образуется небольшой “сивашик“ (мелководный соленый пересыхающий летом водоем). A primary ancient Greek settlement ashore the modern Ak-Mechet bay appeared on the border of V – IV centuries. B.C. It, morally, was related with last “ionian” ancient Greek colonization of North Black sea region. After including of north-western coast of Crimea in the complement of the Chersonese dorian policy in this place the trapezoid in a plan strengthening, consisting of curtain and towers erected in the last fourth of IV c. B.C. This article is devoted to publication of one of them: the tower 6. The general amount of defensive towers within the limits of the Chersonese policy is such (more than 60-ti), that it is time to rise a question about the selection of buildings not only synchronous, but erected by one brigade of masons. For such comparison serves as a reliable criterion not so much linear sizes, how many character of treatment of surfaces of limestone blocks. Exactly the cut of right sides of limestone the hand of master is the best of all looked over.